Efektivitas Pelayanan Terpadu Satu Pintu (PTSP) di Kantor Urusan Agama (KUA) Kota Palembang - Azhari, Ari; Ovianti, Ayu Andini; HAK, Nurmala; Zuraidah, Zuraidah (Berasan: Journal of Islamic Civil Law, 2023)
This research is motivated by regulations made and implemented by the Ministry of Religious Affairs in advancing the best service for the community. Based on this background, in this study there are two formulations of problems, namely 1) How to Implement One-Stop Integrated Services (PTSP) at the Office of Religious Affairs (KUA) Palembang City, 2) How is the Public View of One-Stop Integrated Services (PTSP) at the Office of Religious Affairs (KUA) Palembang City. The method used in this study is a descriptive qualitative method with data collection obtained from interviews and docuemtation at institutions and also the community and taking samples at 6 (six) Religious Affairs Offices (KUA) in Palembang city, namely 1) KUA Ilir Timur II, 2) KUA Ilir Barat I, 3) KUA Seberang Ulu I, 4) KUA Sukarami,Â  5) KUA Kalidoni, 6) KUA Sematang Bform. The results obtained in this study are that the implementation of the One-Stop Integrated Service (PTSP) at the Palembang City Religious Affairs Office makes a good service flow and is arranged in such a way that later it can provide services that are fast, easy, precise, and as needed through a clear flow and of course minimize illegal levies and in the view of the community the application of services at the Office of Religious Affairs (KUA) is very helpful.Â  Because, with this service can be beneficial for the community because it can make it easier for people to request and receive services properly, quickly and easily.